Press play [videorecording (DVD)] - Rugaard, Clara, 1997-; Pullman, Lewis, 1993-; Glover, Danny; Okano, Lyrica (Paramount, 2022)
Laura and Harrison have the picture-perfect romance built on the foundation of a shared love of music. After a deadly accident, Laura is given the chance to save the love of her life when she discovers that their mixtape can transport her back in time.